KR-31761, a Novel K+ATP-Channel Opener, Exerts Cardioprotective Effects by Opening Both Mitochondrial K+ATP and Sarcolemmal K+ATP Channels in Rat Models of Ischemia/Reperfusion-Induced Heart Injury - Min-Kyu Yang; Sung-Hun Lee; Ho-Won Seo; Kyu-Yang Yi; Sung-Eun Yoo; Byung-Ho Lee; Hun-Jong Chung; Hyung-Sik Won; Chang-Soo Lee; Suk-Hyung Kwon; Wahn-Soo Choi; Hwa-Sup Shin (Elsevier, 2009)
The cardioprotective effects of KR-31761, a newly synthesized K+ATP opener, were evaluated in rat models of ischemia/reperfusion (I/R) heart injury. In isolated rat hearts subjected to 30-min global ischemia/30-min reperfusion, KR-31761 perfused prior to ischemia significantly increased both the left ventricular developed pressure (% of predrug LVDP: 17.8, 45.1, 54.2, and 62.6 for the control, 1 μM, 3 μM, and 10 μM, respectively) and double product (DP: heart rate × LVDP; % of predrug DP: 17.5, 44.9, 56.2, and 64.5 for the control, 1 μM, 3 μM, and 10 μM, respectively) at 30-min reperfusion while decreasing the left ventricular end-diastolic pressure (LVEDP). KR-31761 (10 μM) significantly increased the time to contracture during the ischemic period, whereas it concentration-dependently decreased the lactate dehydrogenase release during reperfusion. All these parameters were significantly reversed by 5-hydroxydecanoate (5-HD, 100 μM) and glyburide (1 μM), selective and nonselective blockers of the mitochondrial K+ATP (mitoK+ATP) channel and K+ATP channel, respectively. In anesthetized rats subjected to 30-min occlusion of left anterior descending coronary artery/2.5-h reperfusion, KR-31761 administered 15 min before the onset of ischemia significantly decreased the infarct size (72.2%, 55.1%, and 47.1% for the control, 0.3 mg/kg, i.v., and 1.0 mg/kg, i.v., respectively); and these effects were completely and almost completely abolished by 5-HD (10 mg/kg, i.v.) and HMR-1098, a selective blocker of sarcolemmal K+ATP (sarcK+ATP) channel (6 mg/kg, i.v.) administered 5 min prior to KR-31761 (72.3% and 67.9%, respectively). KR-31761 only slightly relaxed methoxamine-precontracted rat aorta (IC50: >30.0 μM). These results suggest that KR-31761 exerts potent cardioprotective effects through the opening of both mitoK+ATP and sarcK+ATP channels in rat hearts with a minimal vasorelaxant effect. Keywords:: KR-31761, cardioprotection, KATP, ischemia/reperfusion, rat heart